Burnout and its consequences among forensic personnel. Relationship with shame and guilt - López-Andreu, Eugenia Eugenia (2023)
Background: The work of forensic personnel is a source of daily exposure to very stressful situations and may be the origin of burnout. Objectives: The objective of the study was to analyze the prevalence of burnout and its consequences in a sample of 79 workers from the Institute of Legal Medicine (IML) of Valencia (Spain). Method: For the collection of information, the "Spanish Burnout Inventory” (SBI) was applied, and questionnaires to evaluate its consequences (disorders of health and job satisfaction), as well as scales to measure levels of guilt and shame. Results: It was found that IML staff have a moderate risk of professional burnout, with the psychic exhaustion variable being the one that most strongly predicts health consequences. In reference to the role of emotions in Burnout, the highest prevalence were found for guilt and shame, being associated with the appearance of health problems. Conclusions: The IML staff requires work plans and programs that take into account their high level of demand, in order to avoid the appearance of burnout.